Analisis Media Loose Part Untuk Meningkatkan Kemampuan Motorik Halus Anak Usia Dini - Ardiana Nur Maulida Hakim; Sumarno Sumarno; Ida Dwijayanti (Institut Nalanda, 2023)
This article discusses loose part media learning that needs to be developed to become a teaching material media that can be used by early childhood. This loose part media can develop various aspects, especially in fine motor aspects. Loose part media is one of the media that can be arranged, assembled, combined, moved and others according to the wishes and needs of the child. This study aims to determine the learning of loose part media to improve children's fine motor skills. The research method that can facilitate this analysis is a descriptive method for quantitative methods. Data collection techniques used are through observation and interviews. In conclusion, the existence of loose part-based learning media will increase children's creativity and fine motor skills in learning activities in class.